Usability of an Educational Intervention to Overcome Therapeutic Inertia in Multiple Sclerosis Care - Saposnik, Gustavo; Tobler, Philippe N.; Caceres, Fernando; Terzaghi, Maria A.; Ruff, Christian; Maurino, Jorge; Fruns Quintana, Manuel; Oh, Jiwon; Montalban, Xavier; Mamdani, Muhammad (Frontiers in Neurology, 2018)
Background: Educational interventions are needed to overcome knowledge-to-action gaps in clinical care. We previously tested the feasibility and potential efficacy of an educational intervention that facilitates treatment decisions in multiple sclerosis care. A demonstration of the usability of such an intervention is crucial prior to demonstration of efficacy in a large trial. Objectives: To evaluate the usability of a novel, pilot-tested intervention aimed at neurologists to improve therapeutic decisions in multiple sclerosis (MS) care. Methods: We surveyed 50 neurologists from Chile, Argentina, and Canada randomized to an educational intervention arm of a pilot feasibility study using the System Usability Score (SUS) to assess the usability of a traffic light system (TLS)-based educational intervention. The TLS facilitates therapeutic decisions, allowing participants to easily recognize high-risk scenarios requiring treatment escalation. The SUS is a 10 item, validated questionnaire with five response options. The primary outcome was the average and 95% confidence interval (CI) of the SUS score. Values above 68 are considered highly usable. Results: Of 50 neurologists invited to be part of the study, all completed the SUS scale and the study. For the primary outcome, the average usability score was 74.7 (95%CI 70.1-79.2). There was one outlier with a score of 35. The usability score excluding the outlier was 76.8 (95%CI 72.7-80.8). Multivariable analysis revealed no association between participants’ characteristics and the SUS score. Conclusions: Our educational intervention has shown high usability among neurologists. The next step is to evaluate the effectiveness of this educational intervention in facilitating treatment decisions in the management of multiple sclerosis in a large trial.